(3cJGH GdQhVI ef cJGH GdcGajs - (3eMeO Hf jYbhH Hf ESMGb, CHh LYaQ Gdcdjfj,J (B329 (3g` s ((3GHf TeS GdOjf eMeO eMeO TajY s)
(3ChdgG (B:s
(3agPG cJGH GdQhVI ef cJGH GdcGaj ddTjN GdYGde eMeO Hf jYbhH Gdcdjfj HSe Gddg GdQMef GdQMje CeG HYO aGSCdhG QHce GdYGajI hYdjce HGdOYI hGdhbGQ hGdScjfI s
(3BNQgG (B:s
(3bGd CHhLYaQ Ydjg GdSdGe hCJGg QLd abGd dg Efce Cgd HjJ QMeI Je cJGH GdQhVI ef cJGH GdcGaj dCHj LYaQ eMeO Hf jYbhH Gdcdjfj s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B145s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs